Simultaneous Detection of Phillyrin and its Three Metabolites in Rat Bile, Excrement and Urine via HPLC-ESI-MS/MS Quantitative Method - Liu, Xizhe; Li, Feigao; Zhang, Lantong (Current Pharmaceutical Analysis, 2022)
Introduction: Phillyrin, the main pharmacological component of Forsythia suspensa, exhibits a wide variability of therapeutic activities, such as anti-oxidative stress, free radicalclearing, antibacterial activity, hepatic protection, restoration of endothelial glycocalyx damage, prevention of bone loss, attenuation of inflammatory responses, and so on. Previous research has found that phillyrin is not easily absorbed by the body and is rarely excreted into bile, excrement and urine, suggesting that phillyrin circulates primarily in the form of metabolites. Materials and Methods: In the present study, HPLC-ESI-MS/MS method was used for the simultaneous detection of phillyrin and its three metabolites in rat bile, excrement and urine samples. Liquid-liquid extraction with ethyl acetate was carried out for the pretreatment of bile and urine samples, while excrement samples were subjected to ultrasonic pretreatment with acetone. Chromatographic separation was performed on a C18 column with gradient elution. A tandem mass system coupled with a TurboIonSpray interface operating in simultaneous positive and negative ion multiple reaction monitoring modes was employed for the simultaneous detection of the analytes. Results: The proposed method demonstrated excellent accuracy and repeatability. Conclusion: This method was successfully applied for the pharmacokinetic evaluation of phillyrin and its three metabolites simultaneously.
Keywords: excretion